Cream of ricotta flavored with flaxseed flour (Research, Society and Development, 2020)
The present study was developed at the Goiano Federal Institute - Campus of Rio Verde - Go. Whey was once considered a by-product for the food industry, with new technological developments became a coproduct capable of being ingested in the food industry. Ricotta cream flavored with flaxseed flour and oregano developed the following raw materials: milk, whey, ricotta, flaxseed flour, oregano and sodium chloride. Eight formulations with different proportions of flax flour and sodium chloride were submitted to sensory analysis, and the 2 best formulations were chosen for the physicochemical analyzes (Fat, proteins, ash, titratable acidity, dry matter, texture and fat in the dry extract). The analyzes carried out followed the methodology of Normative Instruction No. 22, dated 04/14/2003. The objective of the research was to develop ricotta cream spiced with flaxseed flour and oregano, making a food functional and healthy. To evaluate the physico-chemical characteristics of the 2 best formulations, sensorial analysis regarding the characteristics of the product and purchase intention. It was concluded that the processing of cream of ricotta flavored with linseed flour and oregano met the expectations expected with acceptability of the evaluators, the results of the microbiological analyzes were within the values established by the legislation, and the evaluation of the purchase intention showed that the product had acceptance and acceptance of 52% of purchase intention.